Pengelolaan Sisa Lebih Dana Kapitasi di Fasilitas Kesehatan Tingkat Pertama Milik Pemerintah (Monitoring dan Evaluasi Jaminan Kesehatan Nasional di Indonesia) - M Faozi Kurniawan; Budi Eko Siswoyo; Aulia Novelira; Dedik Sulistiawan; Wan Aisyah; Welly Gadistina; Golda Kurniawati (Center for Health Policy and Management, 2017)
ABSTRACTBackground: During the two years of implementation of the National Health Insurance (JKN), many national and district regulations have been published and revised. However, there is no clear regulation in the management of unutilized capitation fund. The high actual capitation in line with the low utilization ratio, which means it could potentially lead unutilized capitation. Financial management in the district that has not been integrated with unutilized capitation become a challenge for the Puskesmas to accommodate the operational requirements of service.Objective: To analyze the potential and the management of unutilized capitation of JKN program at the Puskesmas and its determinant factorsMethod: This is a case study using cross sectional design and implementation research approach. A total of 492 samples in 13 regionals and 26 districts were selected using multistage random sampling. Primary data were collected through series of interviews and FGDs using a standardized questionnaire. Variables that become secondary data (2014-2015) were collected from Puskesmas and BPJS Kesehatan database. Qualitative data were analyzed using thematic approach and quantitative data were analyzed descriptively and analytically using test for comparison and correlation.Result: Allocation in the utilization of capitation funds, distribution of membership, geographical aspects, service time, the ratio of doctors to the participants, contact rate, total revenue from the Puskesmas have correlation to the unutilized capitation and performance indicators. Planning, budgeting, and disbursement of unutilized capitation follow the budget mechanism of APBD, either early budget document or the mid-year budget document; so it can not be used directly by Puskesmas without submission, reconciliation, and the budget approval from the district government. Nevertheless, the majority of Puskesmas do not manage unutilized capitation because there are no local regulations and technical guidelines for managing unutilized capitation fund.Conclusion: Intervention should consider the variables that had a significant correlation value, both on unutilized capitation and performance indicators. It is necessary to evaluate the fund channeling; and also the strengthening of the regulation should also be followed by optimizing the role BPJS Kesehatan, Health Office, and other stakeholders to support the implementation of the concept of strategic purchasing. Keywords: unutilized fund, capitation, JKN ABSTRAKLatar Belakang: Selama dua tahun penyelenggaraan program Jaminan Kesehatan Nasional (JKN), banyak regulasi nasional dan daerah yang telah diterbitkan dan direvisi. Walaupun demikian, belum ada kejelasan regulasi dalam pengelolaan sisa lebih kapitasi. Tingginya kapitasi aktual sejalan dengan rendahnya rasio utilisasi yang pada akhirnya berpotensi menimbulkan sisa lebih kapitasi. Belum terintegrasinya pengelolaan keuangan daerah dan sisa lebih dana kapitasi menjadi tantangan Puskesmas untuk mengakomodir kebutuhan operasional pelayanan.Tujuan: Menganalisis potensi dan pengelolaan sisa lebih kapitasi JKN di Puskesmas beserta faktor-faktor determinannya.Metode: Studi kasus dengan rancang bangun cross sectional ini menggunakan pendekatan riset implementasi. Sejumlah 492 sampel dari 13 regional dan 26 kabupaten/ kota ditentukan secara multistage random sampling. Data primer dikumpulkan melalui serangkaian wawancara dan FGD menggunakan kuesioner terstandar. Variabel yang menjadi data sekunder (2014-2015) dikumpulkan dari Puskesmas dan BPJS Kesehatan. Data kualitatif dianalisis dengan pendekatan tematik, sementara data kuantitatif dianalisis secara deskriptif dan analitik menggunakan uji komparasi dan uji korelasi.Hasil: Alokasi pemanfaatan dana kapitasi, distribusi kepesertaan, aspek geografis, waktu pelayanan, rasio dokter terhadap peserta, angka kontak, total penerimaan Puskesmas berkorelasi terhadap sisa lebih dana kapitasi dan capaian indikator komitmen pelayanan. Perencanaan, penganggaran, dan pencairan sisa lebih dana kapitasi mengikuti mekanisme APBD baik induk maupun perubahan; sehingga tidak dapat digunakan secara langsung oleh Puskesmas tanpa pengajuan, rekonsiliasi, dan pengesahan dokumen anggaran dari Pemda. Walaupun demikian, sebagian besar Puskesmas belum mengelola sisa lebih dana kapitasi karena tidak ada Peraturan Daerah dan pedoman teknis pelaksanaan.Kesimpulan: Intervensi dapat mempertimbangkan variabel yang memiliki nilai korelasi signifikan, baik terhadap sisa lebih dana kapitasi dan capaian komitmen pelayanan. Selain perlu adanya evaluasi fund channeling; penguatan regulasi sebaiknya juga diikuti dengan optimalisasi peran BPJS Kesehatan, Dinkes, dan stakeholder lainnya untuk mendukung penerapan strategic purchasing. Kata Kunci: sisa lebih, kapitasi, JKN